From Theocentric to Theopraxis: Renegotiating Theology in the Context of the Plurality of Traditions in Asia - Clarence Devadass (International Journal of Indonesian Philosophy & Theology, 2021)
The Church in Asia received first the gift of the Christian faith through missionary activity, starting with the Apostles and then later through the colonial expansion. For a long time, the good news has been spread through various means – conversion, persuasion and sometimes compulsion, primarily when most of Asia was colonized by the ‘Christian West’. The post-colonial era (in Asia) has seen a revival in the Christian faith and many other Asian traditions and religions. Does this now call for a reimagining of what it means to be a ‘Church in Asia’?  The Church in Asia has to “redefine” her mission in the light of the changing socio-economic-political landscape, and for this to happen, there is a need also to look at the merging theology that brings ‘uniqueness’ to the Church in Asia. Here I propose to look at emerging theology as put forward by the Federation of Asian Bishops’ Conferences (FABC) and discover the changing landscape of doing theology from theocentric towards the direction of being theopraxis.